The Relationship Between Fruit and Vegetable Consumption with The Incidence of Anemia Among Adolescent Girls in Three High Schools In Central Maluku - Mailera, Damara Herlis; Asmin, Elpira; Abbas, Mutmainnah; Tahitu, Ritha; Titaley, Christiana Rialine; Seimahuira, Theresia (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Anemia is a global health problem common in both developed and developing countries, often caused by nutritional deficiencies, including low intake of fruits and vegetables. Adolescent girls are particularly at risk due to monthly menstrual blood loss. Objective: This study aimed to analyze the relationship between fruit and vegetable consumption and the incidence of anemia among adolescent girls in three high schools in Central Maluku in 2024. Methods: This was a quantitative analytical study using a cross-sectional design. The population consisted of students from SMA Negeri 15, SMA Negeri 44, and SMA Negeri 48 Central Maluku. A total of 102 respondents were selected using a total sampling technique. Anemia status was measured using the Hemocue device, and data on fruit and vegetable consumption were collected using the Commcare application. Data analysis was performed using the Spearman test. Results: The prevalence of anemia among respondents was 36.3%. Meanwhile, 63.7% reported regularly consuming fruits and 55.9% regularly consumed vegetables. Conclusion: There was no statistically significant relationship between fruit (p = 0.504) and vegetable (p = 0.587) consumption and the incidence of anemia in adolescent girls in the selected Central Maluku high schools in 2024.